Description Of Elderly Independence Level In Fulfillment Of Daily Living Activity At Bane Puskesmas Kota Pematang Siantar In 2022 - Rusmauli Lumban Gaol; Sonia Lumban Tobing (Institute of Computer Science (IOCS), 2022)
The independence of the elderly in completing the Activity of Daily Living (ADL) is defined as a person's independence in carrying out activities and functions of daily life that are routine and usually carried out by humans, and independence in the elderly is important in meeting their basic needs. The older a person is, his physical abilities will decrease, so that it can lead to a decline in his social roles and the functional status of the elderly will decrease and cause dependence to carry out daily activities. This study aims to describe the level of independence of the elderly in fulfilling the Activity of Daily Living (ADL) at the Bane Health Center Pematang Siantar City 2022. This study used a descriptive method with a total sampling technique of 41 respondents. The research instrument used a Katz Index questionnaire. The results of the research on the independence of the elderly in fulfilling the Activity of Daily Living found the elderly with an age range of 60-74 with a level of independent independence 26 respondents (63.4%) and the elderly with an age range of 75-90 years with a level of helped 6 respondents (14.6% ). It can be concluded that the level of independence of the elderly in fulfilling the Activity of daily living at the Bane Health Center Pematang Siantar City 2022 is in the independent category. It’s expected that the elderly are active and participate in socialization and programs carried out by health services regarding independence in carrying out daily activities.